Karakteristik Fisik Beras Analog Instan Berbasis Tepung Jagung dengan Penambahan k-Karagenan dan Konjak - Indah Kurniasari; Feri Kusnandar; Slamet Budijanto (agriTECH, 2020)
Instant analog rice is a form of product development from analog rice that is ready for consumption without the need to be cooked first but only needs to be soaked in boiling water for 3-5 minutes. The main challenge in developing instant analog rice is to reduce rehydration time while maintaining the integrity and texture of the rice produced. Hydrocolloids in the form of κ-carrageenan and konjac with concentrations of 0.5‒10.0%, both as a single additive and in combination, were added to the corn-based analog rice formula. Then, their effects on the physical characteristics of the instant analog rice were studied. The addition of κ-carrageenan and konjac in combination at a concentration of 5% each (KK10) showed the best results. This instant analog rice had a lower degree of breakage and bulk density, 2.02% and 0.39 g/mL, respectively. It showed a more hollow rice microstructure than the control and other combinations. KK10 instant analog rice can be rehydrated by soaking in boiling water for 3.5 minutes. The rehydrated rice had high grain integrity, with hardness, springiness, and chewiness values of 548.14 g; 0.86; and 229.76 g, respectively.